Humoral and cellular immunogenicity and safety following a booster dose of a tetravalent dengue vaccine 5+ years after completion of the primary series in Singapore: 2-year follow-up of a randomized phase II, placebo-controlled trial - Park, Juliana (Hum Vaccin Immunother, 2021)
The tetravalent dengue vaccine (CYD-TDV) is approved for use as a 3-dose series for the prevention of dengue in seropositive individuals ≥9 years. A randomized, placebo-controlled, phase II study of a booster dose of CYD-TDV in individuals who completed the 3-dose schedule >5 years previously (NCT02824198), demonstrated that a booster restored neutralizing antibody titers to post-dose 3 levels. We present additional immunogenicity assessments up to 24 months post-booster, and B- and T-cell responses in a participant subset. Participants aged 9–45 years that had received all three doses of CYD-TDV were randomized 3:1 to receive a booster dose of CYD-TDV (n = 89) or placebo (n = 29). Neutralizing antibody levels at Months 1, 6, 12, and 24 post-booster were assessed by plaque reduction neutralization test. In a subset, B-cell responses were assessed by a fluorescent immunospot assay, and T-cells analyzed by flow cytometry at Days 0, 7, 12, Months 1 and 12. We observed an increase of antibody titers Month 1 post-booster, then a gradual decline to Month 24. In the CYD-TDV booster group, an increase in plasmablasts was seen at Day 7 declining by Day 14, an increase in memory B-cells was observed at Day 28 with no persistence at Month 12. CYD-TDV booster recalled a CD8+ T-cell response, dominated by IFN-γ secretion, which decreased 12 months post-booster. This study showed a short-term increase in antibody titers and then gradual decrease following CYD-TDV booster injection >5 years after primary immunization, and the presence of memory B-cells activated following the booster, but with low persistence.